Immunomonitoring of Human Breast Milk Cells During HCMV-Reactivation - Lazar, Katrin; Kussmann, Thorsten; Pawelec, Graham; Pöschel, Simone; Goelz, Rangmar; Hamprecht, Klaus; Wistuba-Hamprecht, Kilian (Frontiers in Immunology, 2021)
Background: Breast milk leukocytes may play a role in protecting the infant from microbes. The dynamics and the role of lymphocytes in human cytomegalovirus (HCMV)-seropositive mothers shedding HCMV during the first months postpartum (p.p.) into breast milk are mostly unclear. Methods: Breast milk cells were analyzed by Pappenheim panoptic and alpha-naphthyl acetate esterase staining as well as by imaging and polychromatic flow cytometry to simultaneously establish their morphological and phenotypic properties. The latter were characterized in HCMV-seropositive and seronegative mothers´ breast milk cells at different time points p.p. Results: Panoptic staining of breast milk cells revealed the presence of monocytes/macrophages, granulocytes and lymphocytes. Imaging flow cytometry data combined phenotypic and morphological analysis and identified NKT-like cells, NK cells, epithelial cells, T cells and monocytes/macrophages. HCMV-seropositive but not -seronegative mothers had significantly higher T cell frequencies in mature milk. Conclusions: The presence of leukocyte subsets in breast milk may be more influenced by the HCMV-seropositivity of the mother than previously recognized.